2006
DOI: 10.1207/s15327914nc5502_15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Anti-Genotoxic, Anti-Proliferative, and Anti-Metastatic Potential of Crude Watercress Extract in Human Colon Cancer Cells

Abstract: Although it is known to be a rich source of the putative anti-cancer chemicals isothiocyanates, watercress has not been extensively studied for its cancer preventing properties. The aim of this study was to investigate the potential chemoprotective effects of crude watercress extract toward three important stages in the carcinogenic process, namely initiation, proliferation, and metastasis (invasion) using established in vitro models. HT29 cells were used to investigate the protective effects of the extract on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…The present study has focused on watercress, which has a particularly high content of glucosinolates and other potential anticancer phytochemicals including carotentoids. An in vitro study within our laboratory showed that watercress extract can protect cells (HT-29; colon cancer cell line) against DNA damage levels induced by genotoxic agents such as H 2 O 2 and fecal water (33). In the present study, we reported a decrease in all our measures of DNA damage in lymphocytes in response to watercress consumption in humans in vivo.…”
Section: Discussionsupporting
confidence: 67%
“…The present study has focused on watercress, which has a particularly high content of glucosinolates and other potential anticancer phytochemicals including carotentoids. An in vitro study within our laboratory showed that watercress extract can protect cells (HT-29; colon cancer cell line) against DNA damage levels induced by genotoxic agents such as H 2 O 2 and fecal water (33). In the present study, we reported a decrease in all our measures of DNA damage in lymphocytes in response to watercress consumption in humans in vivo.…”
Section: Discussionsupporting
confidence: 67%
“…In general, a decrease in genotoxin-induced DNA damage by plant extracts and an increase in protective enzymes have been observed. In addition in one study with watercress extract, a significant decrease in cell invasion through Matrigel (a model for metastasis) was seen [251] (Table 10). Tables 11 -13 summarise the effects of a range of ITCs and indoles in vitro.…”
Section: Anticancer Effects Of Brassica Vegetables and Components In mentioning
confidence: 99%
“…Over the past 20 years, it has been shown that many classes of phytochemicals are important in the diet and could be used as potential therapeutic tools (Johnson, 2007). However, the scientific investigation on the therapeutic use of watercress and other brassicas is often limited to primary nutrients, GSs, ITCs, and their role as antimutagenic, antigenotoxic, antiproliferative, and antitumoral agents (Boyd et al, 2006). Fewer reports have been published about their richness on phenolic acids, flavonoids, and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%